A Note on the Circulation of Virgil's Eclogues in Renaissance Spain, 1496–1601*. Issue 10 (25th November 2016) - Coroleu, Alejandro
Abstract: The purpose of this essay is twofold. First, I provide an overview of the manuscript and print transmission of Virgil's bucolic verse in Renaissance Spain, both in Latin and in translation. Secondly, I examine how reading Virgil was handled in the Jesuit-founded University of Gandia, as illustrated by some teacher's notes of 1591 (Barcelona, Biblioteca Pública Episcopal MS. 221).